Investigation of Metallo Beta-lactamase Production in Carbapenem Resistant Pseudomonas aeruginosa Isolates (Annals of Medical Research, 2021)
None
Keywords: sem:/emem Pseudomonas Aeruginosa/emem; /emMetallo Beta-Lactamase; Metallo Beta-Lactamase E Test; Combined Disk Test; Polymerase Chain Reaction